2015
DOI: 10.1097/aln.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Readiness after Tricompartment Knee Arthroplasty

Abstract: Compared with a continuous femoral nerve block, a continuous adductor canal block did not appreciably decrease the time to overall discharge readiness even though it did decrease the time until adequate mobilization, primarily because both groups experienced similar analgesia and intravenous opioid requirements that--in most cases--exceeded the time to mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…When comparing the number of patients able to perform TUG test between groups, it was found that ACB was not significantly superior to the FNB at post-anesthesia 48 h2032 (OR = −35.89, 95% CI: −76.35–4.58; P  = 0.08) and 72 h2032 (OR = −35.89, 95% CI: −76.35–4.58; P  = 0.08). However, there were more post-TKA patients able to conduct TUG test in ACB, compared with those in FNB throughout the first 24 h (OR = 23.14, 95% CI: 5.33–100.37; P  < 0.0001) with no heterogeneity (I 2  = 0%, P  = 0.91, Table 4)163233.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…When comparing the number of patients able to perform TUG test between groups, it was found that ACB was not significantly superior to the FNB at post-anesthesia 48 h2032 (OR = −35.89, 95% CI: −76.35–4.58; P  = 0.08) and 72 h2032 (OR = −35.89, 95% CI: −76.35–4.58; P  = 0.08). However, there were more post-TKA patients able to conduct TUG test in ACB, compared with those in FNB throughout the first 24 h (OR = 23.14, 95% CI: 5.33–100.37; P  < 0.0001) with no heterogeneity (I 2  = 0%, P  = 0.91, Table 4)163233.…”
Section: Resultsmentioning
confidence: 94%
“…However, there were more post-TKA patients able to conduct TUG test in ACB, compared with those in FNB throughout the first 24 h (OR = 23.14, 95% CI: 5.33–100.37; P  < 0.0001) with no heterogeneity (I 2  = 0%, P  = 0.91, Table 4)163233.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations